Analysis of Digital Government Implementation in Public Services at the Population and Civil Registration Office of Minahasa Regency - Abdul R. Dilapanga,; Jeane Mantiri,; Gebiyanti Dalipang, (Technium Social Sciences Journal, 2023)
This study aims to describe the application of Digital Government in public services at the Minahasa Regency Population and Civil Registration Office which is not optimal. This study used a qualitative descriptive approach. The results showed that: 1) the availability of digital government software and hardware devices is available, for applications using SIAK and computers are still mostly using old computers 2) human resources are available according to the needs in performing services 3) connectivity used in self-service sometimes still experiences interference with the application, in this case, SIAK whose network is directly provided by the Ministry of Home Affairs center with the implementation of the Directorate General of Dukcapil 4) Stakeholders or parties related to the relationship with DUKCAPIL Minahasa Regency have been underway with 5) financing in supporting the successful implementation of digital government is still experiencing budget limitations